An advanced, ammonia-based combined NOx/SOx/CO2 emission control process towards a low-cost, clean coal technology. (15th February 2020) - Jiang, Kaiqi; Yu, Hai; Chen, Linghong; Fang, Mengxiang; Azzi, Merched; Cottrell, Aaron; Li, Kangkang
Graphical abstract: Highlights: NOx /SOx removal was integrated into NH3 -based CO2 capture in coal power station. The combined NOx /SOx /CO2 removal reduced capital cost by 23.3% in NH3 process. The combined NOx /SOx /CO2 removal reduced CO2 -avoided cost by 17.8% in NH3 process. The combined process has significant cost advantage over separated process. Abstract: Traditional method of removing gas pollutants from a coal-fired power station involves a series of separate processes, which include selective catalytic reduction for NOx treatment, flue gas desulfurisation for SOx removal, and post-combustion CO2 capture. Each of these individual processes involves significant capital investment. To reduce costs, we propose an alternative approach to simultaneously remove these three pollutants by incorporating NOx /SOx treatment into an aqueous NH3 -based CO2 capture process. In our advanced process design, NOx /SOx pollutants are effectively scrubbed by sodium chlorite (NaClO2 ) oxidizing reagent, with the resultant acidic solution efficiently reducing NH3 emissions from CO2 absorber to <1 ppmv. An advanced, NH3 -based flash stripper is used to achieve high capture energy performance, and flue gas heat integration is employed to further reduce the regeneration energy to 2.17 GJ/tonne CO2 . Techno-economic evaluation revealed that our NH3 -based combined NOx /SOx /CO2 removal process has great advantages in capital and energy saving, resulting in a CO2 -avoided cost of 46.2/tonne, which is significantly lower than the cost of the conventional, monoethanolamine-based process (79.1/tonne CO2 ) and the base NH3 process (56.2/tonne CO2 ). This simultaneous NOx /SOx /CO2 capture technology provides an alternative approach to advancing multi-pollutant emission control and CO2 -capture technology, leading to the development of a cost-effective clean coal technology.